STUDY OF SOUND FREQUENCY OF RED SNAPPER (Lutjanus argentimaculatus) AS AN ATTRACTOR (LABORATORY SCALE) - Aristi Dian Purnama Putri; A Asriyanto; Heri Sutanto; W Widiatini (JOURNAL OF COASTAL DEVELOPMENT, 2010)
Fish have spesific characteristic of sound frequency. This sound frequency can be received by fish to responds. Connectivity between sound frequency and fish respond indicates that source of sound frequency has been to function as an attractor. The objectives of this research were to determine the sound frequency of L. argentimaculatus and to describe fish respond of the sound frequency that records as an attractor for fish to find to signal in a laboratory scale. Source of sound frequency was L. argentimaculatus with total length 17 – 22 cm that doing some activities to find feed. Attractor that used in this research was a to research sound editting frequency recording of L. argentimaculatus that was feeding activity and sound of feed target.Lowest frequency range of L. argentimaculatus was 100,8 Hz while highest frequency range was 3244,1 Hz with the intensity range was 30 dB to 57 dB. The significant response time difference of L. argentimaculatus was between morning and daytime observation and between daytime and evening observation.